TINDAK PERLOKUSI DALAM FILM EAT, PRAY, LOVE KARYA RYAN MURPHY SUATU ANALISIS PRAGMATIK - AWON, PRETY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research entitled â€œPerlocutionary Act In The Film Eat, Pray, Love By Ryan Murphyâ€. It is an attempt to identify, classify and analyze the aspects of perlocutionary act from the utterances in the film. The effects of perlocutionary are planned and unplanned effects, while there are sixteen aspects of perlocutionary act. The data were collected from the film by identification and classification the planned and unplanned effect in the conversation. The writer read, watched and looked for the context of conversation by the charactersâ€™ expressions and body language. The collected data have been analyzed by using descriptive method to explain the aspects of perlocutionary act as revealed in the conversation between the characters in the film Eat, Pray, Love. It can be concluded that there are two effects and eleven aspects of perlocutionary act performed in the film. There are nineteen utterances for planned effect and five utterances for unplanned effect. In terms of aspects, there are eleven aspects have been found. They are: bring hearer to know or learn, persuade, impress, encourage, irritate, amuse, get hearer to do,relieve tension, distract attention, embarrass, deceive. The aspects of get hearer to do and irritate were mostly used by the characters in the film. Keywords : Pragmatics, Perlocutionary Act, Film.